CIAT's Tony Bellotti talks about the Cassava Mealybug in SE Asia - Bellotti, T. (2011)
CIAT entomologist Tony Bellotti talks about the Cassava Mealybug in SE Asia, and ways to deal with the spread of the pest and other emerging threats to cassava production in the region.